Modifications of ABLB and Stenger tests for equal bilateral hearing loss (one ear conductive loss; other ear-sensory neural hearing loss or functional hearing loss) cases - Vyasa Murthy MN (Journal of All India Institute of Speech and Hearing, 1971)
ABLB (Alternate binaural loudness balance) and stenger tests are frequently administered in Audiology Clinics for finding recruitment and functional hearing loss in unilateral hearing loss cases respectively. The tests as described by Fowler (1928) and Stenger (Newby 1965) require that the patient should have unilateral hearing loss or he should present a picture of one relatively normal ear and the other ear with some degree of impairment (Sensory neural loss in the case of ABLB). Hence, these tests are considered not useful to cases having bilateral equal hearing loss at all frequencies. But these tests can be modified to cases having equal bilateral hearing loss with one ear conductive loss and the other ear with sensoryneural loss or functional loss. In other words, if the ear contralateral to the conductive loss ear is suspected to have Meniere's disease or functional hearing loss, these tests can be modified and be administered. Conductive loss may be present due to atresia or otitismedia or other causes. This paper explains how these tests can be modified to suit such cases.